(3EOGQI GdGfJGL hGdYdGbGJ GdUfGYjIs - (3GMeO eMeO(B, (3GdeUQjs ((3GdGScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 2008)
(3aj gPG GdcJGH EOGQI GdEfJGL h GdYdGbGJ GdUfGYjI, Gdeaghe GdYGe ddEfJGL hGdJhWf GdUfGYj, hXjaI GdGfJGL h JfXjegG, SjGSGJ GdGfJGL ,GdGQV h eHGfj GdeUfY , OQGSI GdehGO hOQGSI GdGdGJ h GdJLgjRGJ, OQGSI YfUQ GdYed h GdYdGbGJ GdUfGYjIs
(3eQGLY U(B.247s
Keywords: (3GOGQI GdGfJGLs; (3VHW GdGfJGLs; (3YdGbGJ UfGYjIs